Persepsi Analis Kredit Bank Konvensional dan Bank Syariah terhadap Akuntansi dalam Perspektif Syariah - Husna Alia; Rizal Yaya (Journal of Accounting and Investment, 2006)
A number of theories on Islamic accounting have been proposed in the study on Islamic accounting. It shows that there is need for Moslem business organisation to have a different accounting that can direct Muslims towards success not only in the world but also in the Hereafter. This study tries to elaborate the perception of credit analysts in Islamic banking and those in conventional banking in Yogyakarta  on such concepts be implemented by a Muslim business organization. There are four hypotheses being tested. The tests show that there is no significant different perception between the two groups of samples on the characteristics of Islamic business organization, the users of Islamic accounting information, the characteristics of Islamic accounting and the appropriateness of conventional accounting for Muslim business organisation. Although the means are not significantly different, the descriptive statistics shows that the perception of  credit analysts  in Islamic banking is more pragmatic towards Islamic accounting issues rather than those in conventional accounting.